2013
DOI: 10.1002/anie.201209355
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective Synthesis of Epoxides Having a Tetrasubstituted Trifluoromethylated Carbon Center: Methylhydrazine‐Induced Aerobic Epoxidation of β,β‐Disubstituted Enones

Abstract: Scheme 1. Asymmetric aerobic epoxidation of b-trifluoromethyl-b,bdisubstituted enones 1 by a methylhydrazine/base/cinchona alkaloid system. MTBE = methyl tert-butyl ether.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
36
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 97 publications
(37 citation statements)
references
References 52 publications
(14 reference statements)
0
36
0
Order By: Relevance
“…11 Recently, methylhydrazine-induced aerobic epoxidation of b,b-disubstituted enones has been reported. 12 Inspired by these results, we attempted the reaction of 1-indanone-derived b-keto ester 1a with commercially available CH 3 NHNH 2 in combination with Cs 2 CO 3 ( Table 1, entry 1). To our delight, 2a was obtained in 80% yield in 6 h. Then we investigated the influence of the base and hydrazine.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…11 Recently, methylhydrazine-induced aerobic epoxidation of b,b-disubstituted enones has been reported. 12 Inspired by these results, we attempted the reaction of 1-indanone-derived b-keto ester 1a with commercially available CH 3 NHNH 2 in combination with Cs 2 CO 3 ( Table 1, entry 1). To our delight, 2a was obtained in 80% yield in 6 h. Then we investigated the influence of the base and hydrazine.…”
Section: Resultsmentioning
confidence: 99%
“…Shibata reported that methylhydrazine is indispensable for aerobic epoxidation and this phenomenon would not have been discovered using other hydrazine derivatives. 12 We attempted to use different hydrazines to promote this reaction. Nearly no products were obtained when NH 2 15).…”
Section: Resultsmentioning
confidence: 99%
“…and enantioselectivities (96-99 % ee) (Scheme 1). [15] A closely related approach was developed independently by Chen and co-workers. In place of using toxic methylhydrazine, 30 % aqueous H 2 O 2 acted as an oxidant in the catalytic asymmetric epoxidation.…”
Section: Chiral Trifluoromethylated Heterocyclesmentioning
confidence: 99%
“…[26] Thereafter, the same group elaborated a strategically distinct approach for the asymmetric synthesis of chiral 5-CF 3 -2-isoxazoline 8 a via its N-oxide. [27] Building on the use of the asymmetric epoxidation adduct 2 a with the already established synthetic method by the same group, [15] the subsequent Zn/ NH 4 Cl-reduction product (R)-11 underwent an oxidative NÀO coupling reaction mediated by [hydroxyl(tosyloxy)iodo]benzene (HTIB) to form N-oxide (R)-12. The desired product (R)-8 a was generated in 96 % yield in enantiomerically pure form by a deoxygenation reaction with P(OMe) 3 .…”
Section: Chiral Trifluoromethylated Heterocyclesmentioning
confidence: 99%
“…and enantioselectivities (96-99 % ee)( Scheme 1). [15] Ac losely related approach was developed independently by Chen and co-workers. In place of using toxic methylhydrazine, 30 %a queous H 2 O 2 acted as an oxidant in the catalytic asymmetric epoxidation.…”
Section: Chiral Trifluoromethylated Heterocyclesmentioning
confidence: 99%